PELAKSANAAN HUKUM WARIS ISLAM PADA MASYARAKAT SAKAI DI KECAMATAN MANDAU KABUPATEN BENGKALIS PROVINSI RIAU - RATNA PURNAMA SARI BR SIMANJUNTAK (PREMISE LAW JURNAL, 2016)
The kinship system influences the thought and the way of ownership of property and the way how to settle the transfer of property. This can be seen in the practice of distributing inheritance throughout Indonesia and it is practiced by Sakai community in Mandau Subdistrict. Sakai community thats follows matrilineal system is contrary to the Islamic line of descent (bilateral system). Sakai inheritance system which is done collectively is also contrary to the Islamic law which is done individually. The research was about Sakai adat community that was Moslems. It was conducted in Mandau Subdistrict, Bengkalis District, Riau Province. The result of the research showed that the community had known the Islamic inheritance law (faraidh), but not all community had known the Islamic inheritance law (faraidh) which could be seen from the portion of the inheritance. Dispute in distributing inheritance to Sakai community could be settled by reconciliation, either through family reconciliation with or through reconciliation with adat leaders. Keywords: Inheritance Distribution, Reconciliation Deed, Legal Force